Metamorphism and thermal history of the Jaljala Synclinorium, central west Nepal Himalaya - Sharma, Toran; Kizaki, Koshiro (Journal of Nepal Geological Society, 1989)
Present mineralogical studies have revealed the thermal structure of metamorphosed pelitic and semipelitic rock terrains in the five different sections across the Jaljala Synclinorium in the central west Nepal Himalaya. The thermal gradient is estimated from the partitioning of Fe and Mg between the co-existing garnet and biotite. The general trend of the thermal structure is also inferred from the variation of the Na/Na+ K ratio of muscovite in different sections. The observed thermal structure and the metamorphism of the Jaljala Synclinorium is found to be explainable by a frictional shear heating model.